Glacier Outflow Dissolved Organic Matter as a Window Into Seasonally Changing Carbon Sources: Leverett Glacier, Greenland. Issue 4 (23rd April 2020) - Kellerman, A. M.; Hawkings, J. R.; Wadham, J. L.; Kohler, T. J.; Stibal, M.; Grater, E.; Marshall, M.; Hatton, J. E.; Beaton, A.; Spencer, R. G. M.
Abstract: The Greenland Ice Sheet is losing mass at a remarkable rate as a result of climatic warming. This mass loss coincides with the export of dissolved organic matter (DOM) in glacial meltwaters. However, little is known about how the source and composition of exported DOM changes over the melt season, which is key for understanding its fate in downstream ecosystems. Over the 2015 ablation season, we sampled the outflow of Leverett Glacier, a large land‐terminating glacier of the Greenland Ice Sheet. Dissolved organic carbon (DOC) concentrations and DOM fluorescence were analyzed to assess the evolution of DOM sources over the course of the melt season. DOC concentrations and red‐shifted fluorescence were highly associated ( R 2  > 0.95) and suggest terrestrial inputs from overridden soils dominated DOM early season inputs before progressive dilution with increasing discharge. During the outburst period, supraglacial drainage events disrupted the subglacial drainage system and introduced dominant protein‐like fluorescence signatures not observed in basal flow. These results suggest that subglacial hydrology and changing water sources influence exported DOC concentration and DOM composition, and these sources were differentiated using fluorescence characteristics. Red‐shifted fluorescence components were robust proxies for DOC concentration. Finally, the majority of DOM flux, which occurs during the outburst and postoutburst periods, was characterized by protein‐like fluorescence from supraglacial and potentially subglacial microbial sources. As protein‐like fluorescence is linked to the bioavailability of DOM, the observed changes likely reflect seasonal variations in the impact of glacial inputs on secondary production in downstream ecosystems due to shifting hydrologic regimes. Key Points: Dissolved organic carbon concentrations can be estimated in glacial outflow from the fluorescence intensity of red‐shifted fluorescence Optical tracers can be used to differentiate subglacial from supraglacial inputs Optical properties in July highlight microbial sources of dissolved organic matter, with implications for downstream bioavailability